Intercourse of Verbal and Visual Communication with Rock n’ Roll Magazine Reader - ., Naldo (KnE Social Sciences, 2018)
This study aims to determine the correlation between the attractiveness of the delivery messages in the Rolling Stone Indonesia magazine with the fulfillment of information about music. This object is 84 respondents of Rolling Stone Indonesia magazine customer in Bandung. Research methods used in this research is method of survey research techniques to examine the relationship correlation among the variables through hypothetical test. Data were collected from the questioner, interview and study of literature. Ordinal data are tested using the coefficientSpearman Rank correlation. From the data that already collected, the data related to separate the variables and calculated the number of correlation to see the correlation between the data variables. Results of this research is there a correlation between the attractiveness of the delivery messages in the Rolling Stone Indonesia magazine with the fulfillment of information about music about 0.913. Based on the study, it can be concluded that the attractiveness of the delivery messages in the Rolling Stone Indonesia magazine has a significant correlation with the customer fulfillment of information in the Rolling Stone Indonesia magazine. Keywords: mass communication, magazine, messages, music